Pengaruh Pendidikan Islam di PAUDQT Al-Aziz Pati terhadap Perkembangan Karakter Anak - HM, Aminullah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2024)
Technological developments that can be enjoyed by young children, Islamic education has become a bulwark for children so that they are not carried away by the increasingly free flow of progress. Children who are educated with strong religious characteristics will grow a generation that will naturally love their nation and country. Islamic education in early childhood is very important in developing children's character. PAUDQT Al-Aziz aims to develop students who are Quranic, creative, innovative based on Pancasila and Manhaj Ahlussunah Wal Jamaah. From the results of interviews and observations, it is known that the Islamic religious education carried out really helps students' development. Children become more creative, innovative and able to carry out their obligations to pray and recite the Koran. A sense of love for others and the environment is also created thanks to teaching at school. Intense communication between teachers, parents and children really helps the school in achieving its goals.